Decision tree based expert system for power factor improvement under distorted and unbalanced current conditions - Moreira, Alexandre C.; Deckmann, Sigmar M.; Marafão, Fernando P. [UNESP]; da Silva, Luiz C.P.; Paredes, Helmo K.M. [UNESP] (My University, 2015)
This paper proposes a methodology to identify the reactive and harmonic compensation in three-phase power systems. Considering the behavior of power factor, current and voltage harmonic distortion, unbalance factors and reactive power daily variation, the developed tool is able to select two suitable solutions for power factor correction on the installation under analysis. The results gathered from computational simulations, as well as from measuring an industrial facility are presented and discussed. Based on specialist knowledge the developed tool may be very useful for finding the correct compensation solution quickly even manipulating a large amount of data.
Keywords: Active Compensators; Passive Compensators; Power Factor; Reactive and Harmonics Compensation; Selective compensation; STD-1459-2010